Seed Survival at Low Temperatures: A Potential Selecting Factor Influencing Community Level Changes in High Altitudes under Climate Change. (1st November 2020) - Jaganathan, Ganesh K.; Dalrymple, Sarah E.; Pritchard, Hugh W.
Abstract: In alpine ecosystems, imbibed seeds are often exposed to temperatures as low as −35 °C, challenging their survival in the soil. Here, we show that seeds have mechanisms to survive cold climate prevalent in alpine ecosystems and have identified three such mechanisms from existing literature, including two forms of freezing avoidance (the presence of water impermeable seed coats, and the supercooling of seed tissues) and one form of freezing tolerance (by extracellular-freezing). Experimentally-derived published data on the lowest temperature recorded at which 50% of a seed sample survived (i.e., lethal temperature; LT50 ) was used to generate a dataset of 24 species across low altitude, boreal and alpine environments. We assumed that the ability of seeds to maintain viability at very low temperatures would increase in species associated with higher altitudes conferring a competitive advantage that would be lost under projected climate change. However, our results reveal to underpin that seeds from boreal species survive relatively better at lower temperatures than those of alpine species. Paradoxically, a warming climate could lead to alpine seed death due to extremes of cold at the soil surface resulting from snow cover loss, whilst the declining snow cover may facilitate boreal forest colonization above the current treeline.